2013
DOI: 10.1093/annonc/mdt204
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus, insulin treatment, diabetes duration, and risk of biliary tract cancer and hepatocellular carcinoma in a European cohort

Abstract: Background: Evidence on associations between self-reported diabetes mellitus, diabetes duration, age at diabetes diagnosis, insulin treatment, and risk of biliary tract cancer (BTC) and hepatocellular carcinoma (HCC), independent of general and abdominal obesity is scarce. Patients and methods: We conducted a prospective analysis in the EPIC-cohort study among 363 426 participants with self-reported diabetes data. Multivariable adjusted relative risks and 95% confidence intervals were estimated from Cox regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(104 citation statements)
references
References 32 publications
6
96
0
2
Order By: Relevance
“…Similar findings were previously reported in the EPIC cohort and its French sub-cohort for the association between soft drinks and juices and diabetes risk; 350 mL increment of artificially sweetened soft drink had stronger effect on increased risk of developing diabetes than sugar-sweetened soft drink, while juice intake was not associated with diabetes [8,41]. Indeed, a recent study in mice reported an effect of non-caloric artificial sweeteners on intestinal microbiota composition leading to induction of glucose intolerance [42], but the findings require further confirmation in humans.…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings were previously reported in the EPIC cohort and its French sub-cohort for the association between soft drinks and juices and diabetes risk; 350 mL increment of artificially sweetened soft drink had stronger effect on increased risk of developing diabetes than sugar-sweetened soft drink, while juice intake was not associated with diabetes [8,41]. Indeed, a recent study in mice reported an effect of non-caloric artificial sweeteners on intestinal microbiota composition leading to induction of glucose intolerance [42], but the findings require further confirmation in humans.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, DM type 2 can lead to HCC caused by carcinogenic effects on the liver and other tissues from insulinlike growth factor1 (IGF1) due to hyperinsulinaemia and insulinresistance ( Figure 1) [15,16] . The risk for HCC was particularly higher in diabetic patients treated with insulin [17] . However, Yamamoto et al [18] , 2012, reported a case in which a dramatic regression of HCC was observed after four weeks of treatment with a dipeptidyl peptidase4 enzyme (DPP4) inhibitor in a patient with HCVrelated chronic hepatitis.…”
Section: Pathogenesis and Risk Factorsmentioning
confidence: 94%
“…39 For example, the European Prospective Investigation into Cancer and Nutrition found obesity to account for approximately 16% of cases of HCC in Europe. 40 Similarly, based on data from a Surveillance, Epidemiology, and End Results (SEER) analysis of the Medicare population, diabetes and or obesity to contribute to 36.6% of cases of HCC. 41 However, calculation of the PAF assumes that all cases of HCC that develop in patients with metabolic syndrome are etiologically related to this condition, which is unlikely to be true.…”
Section: Preventionmentioning
confidence: 99%